NURONDAIAH - POET’S POEM THOUGHT - Belale, Kumar; Chandrakath, K. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Kannada literature after the twelfth century underwent socio-religious and cultural changes and became the beginning of a new era. The mature Champu literature that emerged with devotion to tradition flourished initially, and then the simple, natural, and popular national rhythm settled in the minds of the people. By using the vernacular as a literary language and expressing it with new power and emotional expression, it gave a thoughtful literature that had never been seen before in the world to global literature. The literary society of the refuges invited a radical change in society and gave the later literature a great intellectual basis as an experience of knowledge. The pride of the vachana literature is that the people’s voice, which spoke for itself and for itself, raised it to the height of the divine voice. Sharanara literature, which was born with the desire to explore life, turned its gaze from the individual to the collective. It absorbed the traditional wisdom and through it, it tried to build a human religion by preaching timeless values. Since then, Kannada literature has taken on a new form and has pioneered the welfare of the people. Such a rich and innovative poetic literature has become a beacon for future literary creation.